2010
DOI: 10.1007/s00726-010-0779-9
|View full text |Cite
|
Sign up to set email alerts
|

Early- and advanced non-enzymatic glycation in diabetic vascular complications: the search for therapeutics

Abstract: Cardiovascular disease is a common complication of diabetes and the leading cause of death among people with diabetes. Because of the huge premature morbidity and mortality associated with diabetes, prevention of vascular complications is a key issue. Although the exact mechanism by which vascular damage occurs in diabetes in not fully understood, numerous studies support the hypothesis of a causal relationship of non-enzymatic glycation with vascular complications. In this review, data which point to an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 117 publications
3
65
0
1
Order By: Relevance
“…Nonenzymatic glycation of proteins or Maillard reaction is increased in diabetes mellitus due to hyperglycemia (Hussain et al, 2008;Cárdenas-León et al, 2009;Hussain et al, 2010;Hussain et al, 2011;Schalkwijk, Miyata, 2012). Numerous synthetic and natural com- pounds with different glycation inhibition mechanisms are reviewed in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Nonenzymatic glycation of proteins or Maillard reaction is increased in diabetes mellitus due to hyperglycemia (Hussain et al, 2008;Cárdenas-León et al, 2009;Hussain et al, 2010;Hussain et al, 2011;Schalkwijk, Miyata, 2012). Numerous synthetic and natural com- pounds with different glycation inhibition mechanisms are reviewed in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that the renal accumulation of AGEs is implicated in the pathogenesis of diabetic vascular complications [52] . As well, AGEs are noted to upregulate the expression of TGF-β and collagen, which accumulates particularly in glomerular and extracellular matrix, thus provoking glomerular hypertrophy in diabetes [53] .…”
Section: Tgf-β Plays An Abysmal Role In Pathogenesis Of Nephropathy: mentioning
confidence: 99%
“…The renowned deleterious effects of AGEs on endothelial function and vessel structure has prompted numerous studies on molecules with promising blocking effects on AGE formation and AGE-receptor (RAGE)-mediated activity, or acting to prevent or disrupt AGEprotein cross-links (reviewed in [192][193][194]). Aminoguanidine is able to inhibit the formation of AGEs by interaction with and quenching of dicarbonyl compounds.…”
Section: Age Inhibitors -mentioning
confidence: 99%